2020
DOI: 10.1038/s41524-020-00416-1
|View full text |Cite
|
Sign up to set email alerts
|

Biquadratic exchange interactions in two-dimensional magnets

Abstract: Magnetism in recently discovered van der Waals materials has opened several avenues in the study of fundamental spin interactions in truly two-dimensions. A paramount question is what effect higher-order interactions beyond bilinear Heisenberg exchange have on the magnetic properties of few-atom thick compounds. Here we demonstrate that biquadratic exchange interactions, which is the simplest and most natural form of non-Heisenberg coupling, assume a key role in the magnetic properties of layered magnets. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
108
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 51 publications
7
108
0
1
Order By: Relevance
“…The fourth term in Eq. (1) represents the biquadratic (BQ) exchange, which involves the hopping of two or more electrons between two adjacent sites 15,16 . Its strength is given by the constant K ij , which is the simplest and most natural form of non-Heisenberg coupling.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fourth term in Eq. (1) represents the biquadratic (BQ) exchange, which involves the hopping of two or more electrons between two adjacent sites 15,16 . Its strength is given by the constant K ij , which is the simplest and most natural form of non-Heisenberg coupling.…”
Section: Resultsmentioning
confidence: 99%
“…Its strength is given by the constant K ij , which is the simplest and most natural form of non-Heisenberg coupling. We recently found that several 2D magnets develop substantial BQ exchange in their magnetic properties, which is critical to quantitatively describe important features such as Curie temperatures, thermal stability, and magnon spectra 16 . The magnitude of K ij for CrCl 3 is 0.22 meV, which is slightly smaller than the BL exchange for the first-nearest neighbors J 1 = 1.28 meV but too large to be ignored.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the energy-mapping method, exchange and SW energy increase with U, worsening the agreement between theory and INS measurements. This suggests that non-Heisenberg interactions, such as biquadratic exchange or multisite exchange interactions [56][57][58][59][60] , might be important in this system, especially when additional electron correlations are taken into account. By analogy with transition-metal oxide systems 57 one can assume that the induced magnetic polarization on iodine ligands can play a decisive role in this non-Heisenberg behavior.…”
Section: Exchange Parametersmentioning
confidence: 99%